Folic acid-tethered Pep-1 peptide-conjugated liposomal nanocarrier for enhanced intracellular drug delivery to cancer cells: conformational characterization and in vitro cellular uptake evaluation - Kang MJ (Dove Medical Press, 2013)
Myung Joo Kang, Sang Han Park, Mean Hyung Kang, Min Jung Park, Young Wook Choi College of Pharmacy, Chung-Ang University, Seoul, Korea Background: A novel dual ligand–modified liposome, folic acid-tethered Pep-1 peptide-conjugated liposomal nanocarrier (FP-Lipo), was designed to overcome the nonselectivity of conventional penetrating peptide-tagged nanoparticulates and to provide the advantage of selective targeting of the folic acid receptor, which is frequently overexpressed on epithelial cancer cells. Methods: FP-Lipo was prepared by a sequential process of formation of a maleimide-derivatized small unilamellar vesicle, postinsertion of distearoyl phosphatidyl ethanolamine-polyethylene glycol 2000–folate to the vesicle, and Pep-1 peptide conjugation via thiol-maleimide linkage. Conformational and physical characteristics of the FP-Lipo nanocarriers were investigated for the extent of Pep-1 peptide and folic acid on the surface, vesicle size, and zeta potential. In vitro cellular uptake behaviors of the novel carrier containing a fluorescein dextran isothiocyanate probe were examined by spectrophotometry or by confocal laser scanning microscopy. Results: A novel nanocarrier bearing approximately 750 folate ligands and 100 penetrating peptides per vesicle was successfully prepared. The physical properties were as follows: 140 nm in size; 5 mV in zeta potential; less than 0.3 in polydispersity index. An in vitro cellular uptake study revealed that the FP-Lipo nanocarrier system exhibited more than twofold enhanced translocation into the folic acid receptor–positive HeLa cells compared with the single Pep-1 peptide–modified liposome. Meanwhile, its cellular association and internalization into the folic acid receptor–negative normal HaCaT cells was comparable with that of Pep-1 peptide–modified liposome. Conclusion: An advanced dual ligand-modified liposome is potentially useful for the treatment of folic acid receptor–positive tumors with high translocation capability of the penetrating peptide–modified liposome. Keywords: liposome, folic acid, Pep-1 peptide, cell-penetrating peptide, intracellular delivery, targeted delivery